1996
DOI: 10.1101/gad.10.14.1763
|View full text |Cite
|
Sign up to set email alerts
|

Differential splicing-in of a proline-rich exon converts alphaNAC into a muscle-specific transcription factor.

Abstract: NAC (nascent polypeptide-associated complex) was recently purified as an a/p heterodimeric complex binding the newly synthesized polypeptide chains as they emerge from the ribosome. We have identified, cloned, and characterized a muscle-specific isoform of aNAC. The 7.0-kb mRNA arises from differential splicing-in of a 6.0 kb-exon giving rise to a proline-rich isoform that we termed skNAC. The skNAC protein was specifically expressed in differentiated myotubes but not in myoblasts. We have identified a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 46 publications
6
97
1
1
Order By: Relevance
“…Interestingly, it had been recently reported that ␣NAC binds to DNA in a sequence-specific manner. A consensus sequence for binding of ␣NAC to DNA was published (5Ј-(G/C)(G/ C)A(G/C)A(G/C)ANNNG-3Ј) (25). We confirmed binding of ␣NAC to oligonucleotides containing this motif; however, we also observed binding to oligonucleotides where this motif was mutated (data not shown).…”
Section: Fig 4 Recombinant Nac Interacts With Nascent Chains On Ribsupporting
confidence: 58%
“…Interestingly, it had been recently reported that ␣NAC binds to DNA in a sequence-specific manner. A consensus sequence for binding of ␣NAC to DNA was published (5Ј-(G/C)(G/ C)A(G/C)A(G/C)ANNNG-3Ј) (25). We confirmed binding of ␣NAC to oligonucleotides containing this motif; however, we also observed binding to oligonucleotides where this motif was mutated (data not shown).…”
Section: Fig 4 Recombinant Nac Interacts With Nascent Chains On Ribsupporting
confidence: 58%
“…NACA appears to be part of the chaperon system that ensures the proper folding of nascent proteins, notably those to be translocated in the endoplasmic reticulum, ER 12,13 . The naca gene also encodes a muscle-specific, much larger isoform, skNAC, through differential RNA splicing 14,15 . NACA and skNAC have also been described as transcriptional co-activators in osteoblasts and myotubes, respectively 14,16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…The naca gene also encodes a muscle-specific, much larger isoform, skNAC, through differential RNA splicing 14,15 . NACA and skNAC have also been described as transcriptional co-activators in osteoblasts and myotubes, respectively 14,16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 lists proteins for which we have used strains of E. coli that over-express Hsp90 (Plus90α™; Plus90β™; Expression Technologies Inc., San Diego, CA) to prevent aggregation during expression [45][46][47][48][49][50][51][52]. This illustrates the structural and functional disparity among the in vitro clientele of Hsp90.…”
Section: Hsp90 Client Proteinsmentioning
confidence: 99%